INFORMATION TECHNOLOGIES FOR THE ANALYSIS OF THE STRUCTURAL CHANGES IN THE PROCESS OF IDIOPATHIC MACULAR RUPTURE DIAGNOSTICS - Pavlov, Sergii; Saldan, Yosyp; Vovkotrub-Lyahovska, Dina; Saldan, Yuliia; Vassilenko, Valentina; Yakusheva, Yuliia (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2019)
Process of eye tomogram obtaining by means of optical coherent tomography is studied.Stages of idiopathic macula holes formation in the process of eye grounds diagnostics are considered. Main stages of retina pathology progression are determined: Fuzzy logic units for obtaining reliable conclusions regarding the result of diagnosis are developed. By the results of theoretical and practical research system and technique of retinal macular region of the eye state analysis.